PERANAN ORANG TUA DALAM MENDIDIK ANAK SECARA ISLAMI - Hasbiyallah Hasbiyallah; Kasmin Kasmin; Mahlil Nurul Ihsan (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
The family was as the first education, the main and oldest, which functions as the foundation stone or foundation for morality and religious education (social and moral education). Education in family, usually natural or informal. But if the education in the family business that fails, will form a child who tends to be lazy child to learn, so that children's achievement will never be in line with expectations. This study aims to determine the role of parents towards Islamic education, factors of non-performance of Islamic religious education, and the role of parents to inculcate Islamic religious education for children in industrial environments. Parents' role in educating children Islamically include instilling good values religious education through personal development of children, develop the child's religious education and ethical guidance for daily life. Â Kata kunci: peranan, orang tua, pendidikan Islam dan anak.